Accumulation of cadmium in growing peanut (Arachis hypogaea L.) seedlings - its effect on lipid peroxidation and on the antioxidative enzymes catalase and gualacol peroxidase - Kumar, Sunil; Mehta, Urmil J.; Hazra, Sulekha (Journal of Plant Nutrition and Soil Science, 2008)
In plants exposed to high metal concentrations, mechanisms to counteract the oxidative burst are crucial for its survival. To investigate the temporal sequence of physiological reactions of peanut seedlings (Arachis hypogaea L.) to cadmium exposure, seeds were cultured in increasing concentrations of CdCl(2), ranging from 50 to 300 mu M. Germination frequency was scored, and the distributions of Cd in root, stem, and leaves were determined after 2 and 4 weeks of culture. Lipid peroxidation and activities of antioxidative enzymes including catalase (CAT, EC 1.11.1.6) and guaiacol peroxiclase (GPX; EC 1.11.1.7) were estimated in these three parts of the plant. Germination of seedlings was not affected, but the growth of seedlings was severely suppressed with increasing concentrations of CdCl(2) and incubation period. Pattern of Cd distribution in the three organs varied with concentration and period of exposure to Cd. Increased lipid peroxidation was detected in all parts of the developing seedlings with increasing metal accumulation. Catalase and guaiacol peroxidase activity varied in the three parts of the seedlings with concentration of Cd and incubation period. Guaiacol peroxidase activity appears to be more active in scavenging the reactive oxygen species in developing peanut seedlings. The results of the present experiment demonstrate the advantages of a tissue-culture model system in studying the complex network of interactions of various factors in stress tolerance.
Keywords: Abiotic stress; heavy metal; stress tolerance; TBARS; thiobarbituric acid; Tissue culture

Differential accumulation of manganese in three mature tree species (Holoptelia, Cassia, Neem) growing on a mine dump - Raju, D.; Kumar, Sunil; Mehta, Urmil J.; Hazra, Sulekha (Current Science, 2008)
Three trees, including Cassia siamea (Cassia), Azadirachta indica (Neem), Holoptelia integrifolia (Holoptelia) belonging to three different families were identified from a manganese mine tailing dump. Manganese content in dump soil and in the stem, green leaves and dry, fallen leaves of the plants was determined. Values were compared with similar samples collected from normal vegetation. Under control condition, manganese content was highest in Cassia. Distribution of metal in samples collected from the dump site revealed that Holoptelia has a special ability to accumulate high amounts of manganese under stress condition followed by Cassia and Neem. There is no literature on metal accumulation in Holoptelia. Mechanism of manganese sequestration in Holoptelia is different from the other two trees growing in the same soil.
Keywords: Azadirachta indica; Cassia siamea; Holoptelia integrifolia; hyperaccumulator; manganese; mine dump

Ultrafast switching time and third order nonlinear coefficients of microwave treated single walled carbon nanotube suspensions - Kamaraju, N.; Kumar, Sunil; Karthikeyan, B.; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K.; Sood, A. K. (Journal of Nanoscience and Nanotechnology, 2009)
Microwave treated water soluble and amide functionalized single walled carbon nanotubes have been investigated using femtosecond degenerate pump-probe and nonlinear transmission experiments. The time resolved differential transmission using 75 femtosecond pulse with the central wavelength of 790 nm shows a bi-exponential ultrafast photo-bleaching with time constants of 160 fs (130 fs) and 920 fs (300 fs) for water soluble (amide functionalized) nanotubes. Open and closed aperture z-scans show saturation absorption and positive (negative) nonlinear refraction for water soluble (amide functionalized) nanotubes. Two photon absorption coefficient, beta(0) similar to 250 cm/GW (650 cm/GW) and nonlinear index, gamma similar to 15 cm(2)/pW (-30 cm(2)/pW) are obtained from the theoretical fit in the saturation limit to the data for two types of nanotubes.
Keywords: Nonlinear Optical Coefficients; SWCNT; Ultra-Fast Switching